DISPOSAL OF THE EXCLUSIVE RIGHT TO INTELLECTUAL PROPERTY OBJECTS - Kayupov Alisher Turayevich (Scholar Express Journals, 2024)
In this article the concept of intellectual rights is discussed as well as the most important problems of intellectual property’s transfer and the ways to solve these problems. The article is devoted to a comprehensive study of ways to transfer exclusive (intellectual property) rights. The characteristic features of licencing agreements, alienation agreements and other agreements in the field of intellectual property transfer are highlighted and described. This article is an attempt to reveal the main causes of the legislation’s imperfection as a consequence of the lack of theoretical research in this area. The legal nature of the agreement on the transfer (sail) of intellectual property is determined. Substantial restrictions on the transfer of intellectual property by primary owners are proposed. A new criterion of intellectual property law theory is highlighted. The new author’s classification of intellectual property contracts is given. We propose measures to improve the legal regulation of pledge in intellectual property law. The main problems of exclusive rights and authorised (share) capital and options for overcoming them are given. The practical and theoretical problems of applying commercial concession (franchising) are analysed, a new criterion of legal relations related to commercial concession is proposed. All the proposed conclusions are the result of a long scientific work and practical protection of intellectual property rights as an attorney at law.
Keywords: Intellectual property rights; exclusive rights; copyright